Sexual exploitation in childhood and adolescence: daily lives and perspectives - Quitéria Clarice Magalhães Carvalho; Mirna Albuquerque Frota (Rev Rene)
Sexual exploitation in childhood and adolescence consists of a complex phenomenon, emerging from the materialization of social, economical, cultural, juridical, political and psychological gaps. The aim was to describe the daily lives of sexually exploited children and adolescents, and to identify the causing factors that lead the child to stay in the streets; to investigate the sexually exploited children’s and adolescents’ perspectives for life in the future. Ethnographic research having as a setting the Beira Mar Avenue and a Non-Governmental Organization in Fortaleza, in the State of Ceará. The subjects were children and adolescents within the age group ranging from 10 to 16 years old. The data were collected through participant observation and semi-structured interviews. The analysis consisted of the comprehension, documentation, and categorization of the accounts. Thematic categories emerged: The Wandering; The Intra-familiar violence; Being rich to be happy. It has been concluded that the victims of that scourge are mostly economically oppressed children and adolescents, who come from families aggrieved by poverty and permeated by abuse and violence.